2015
DOI: 10.1097/mej.0000000000000132
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality and live simulation

Abstract: Virtual reality simulation proved to be a valuable tool, equivalent to live simulation, to test medical students' abilities to perform mass casualty triage and to detect improvement in such skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…51 For simulation of various types, hospitals can use live moulaged actors (actors with mock injuries to very realistic extend and instructed scenario role play), computerized patients, high-fidelity simulators and virtual reality, amongst others. 50,[52][53][54][55][56][57][58] Live moulaged actors seemed to have the highest fidelity with students showing more accurate and more timely performance in one study of a small number of paediatric MCI victims but a large set of tested participants. 50 In another recent study, virtual reality simulation proved to be valuable.…”
Section: Simulation Strategiesmentioning
confidence: 90%
See 1 more Smart Citation
“…51 For simulation of various types, hospitals can use live moulaged actors (actors with mock injuries to very realistic extend and instructed scenario role play), computerized patients, high-fidelity simulators and virtual reality, amongst others. 50,[52][53][54][55][56][57][58] Live moulaged actors seemed to have the highest fidelity with students showing more accurate and more timely performance in one study of a small number of paediatric MCI victims but a large set of tested participants. 50 In another recent study, virtual reality simulation proved to be valuable.…”
Section: Simulation Strategiesmentioning
confidence: 90%
“…50 In another recent study, virtual reality simulation proved to be valuable. 52 All simulation techniques in these studies focused on clinical patient triage. To our knowledge, which method best simulates the role of radiology during DMP activation has not been specifically studied.…”
Section: Simulation Strategiesmentioning
confidence: 99%
“…However, those studies evaluating an interactive procedure, such as mass casualty triage, have had more mixed results, not offering enough argument to suggest widespread use and investment [ 12 , 24 - 28 ]. Although most participants enjoy the experience, the performance measures do not uniformly improve over alternative modalities, such as live simulation [ 12 , 24 ] or card sort triage [ 27 ]. Such results continue to call into question the true value of virtual reality.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that virtual reality is well accepted, and some have demonstrated its validity for skills training, with particularly good evidence in surgical fields [ 6 - 11 ]. However, studies assessing its effectiveness in team training and patient care scenarios has been limited [ 12 - 14 ]. A recent meta-analysis by Cook indicated that virtual reality performed better than no intervention, but not better than other instructional designs [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Implementing such training in a virtual environment offers several advantages, including overcoming logistical challenges (eg, facilities and scheduling) associated with physical simulation [9]. Studies have shown that the use of virtual simulations was found to be as effective as physical simulation in improving performance in acute care [10,11]. Blending virtual and physical simulations may optimize learning effectiveness [12].…”
Section: Introductionmentioning
confidence: 99%